Identification of immunodominant CD4-restricted epitopes co-located with antibody binding sites in individuals vaccinated with ALVAC-HIV and AIDSVAX B/E. - Silvia Ratto-Kim; Mark S de Souza; Jeffrey R Currier; Nicos Karasavvas; John Sidney; Morgane Rolland; Anais Valencia-Micolta; Sirinan Madnote; Alessandro Sette; Sorachai Nitayaphan; Punnee Pitisuttuthum; Jaranit Kaewkungwal; et al. (PLoS ONE, 2015)
We performed fine epitope mapping of the CD4+ responses in the ALVAC-HIV-AIDSVAX B/E prime-boost regimen in the Thai Phase III trial (RV144). Non-transformed Env-specific T cell lines established from RV144 vaccinees were used to determine the fine epitope mapping of the V2 and C1 responses and the HLA class II restriction. Data showed that there are two CD4+ epitopes contained within the V2 loop: one encompassing the α4β7 integrin binding site (AA179-181) and the other nested between two previously described genetic sieve signatures (AA169, AA181). There was no correlation between the frequencies of CD4+ fine epitope responses and binding antibody.